State Defense Attitudes and Religious Values In The Use of Masks to Prevent Covid-19 at Senior High Scool PK Muhammadiyah Kartasura - Nafilla Titan Prasetya; Dwi Linna Suswardany (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
This research aims to determine the influence of knowledge in creating a sense of participation in national defense among students to prevent the increase in Covid-19 cases in Indonesia. The method used was pre-experimental with a one-group pre-test and post-test design approach. This research was carried out among all 10th grade students at SMA PK Muhammadiyah Kartasura on 22 October 2022 with a population of 215 people. This research used non-probability sampling with a purposive sampling technique with a total of 30 respondents who met the inclusion and exclusion criteria. Analysis was carried out using the normality statistical test, the paired sample t test, and the Wilcoxon test. This research uses data analysis based on the use of software in the form of the SPSS application. The research results show that the sig. 0,000 The results of the paired sample t test on education show that there is an influence between the respondent's knowledge before being given education and Pancasila values, as well as religious values and after being given education. The results of statistical processing carried out using the Wilcoxon attitude test show a sig value. 0.000 indicates that there is a significant influence on respondents' attitudes before being given education and Pancasila values, as well as religious values and after being given education. In conclusion, there is a significant influence between education, respondents' attitudes before being given education and Pancasila values, as well as religious values and after being given education. Keyword: Covid-19, Defending The Country, Religious Values